Optimasi Business Process Improvement Berbantuan Metode FLASH dengan Integrasi API Trello - Hilmi Aziz Bukhori Bukhori; Bayu Rahayudi; Widhy Hayuhardhika Nugraha Putra (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
The emergence of the COVID-19 case has a major impact on all sectors. At this critical time, customer satisfaction can be done by optimizing the use of resources by implementing BPI. The BPI method will conduct a review regarding the resources owned and will be adjusted to the current conditions. BPI is closely related to changes in project management. One of the optimal methods used in project management is FLASH, where the project duration will be in the form of a more flexible time interval. In this research, the system also uses Trello as a project management application. The purpose of this research is to design a scheme for calculating the duration of the project, as well as mapping project management from the data tasks that are owned using the FLASH method. System testing on the fuzzy system algorithm is implemented on the AOA network. Based on the calculation on the test object carried out, the probability of completing the project on time is 76%. This amount is obtained from the average delay factor for each task. With these values, scheduling using the FLASH method obtained the fastest duration is 19 days and the latest is 30 days.